Hyperoside ameliorates cerebral ischaemic–reperfusion injury by opening the TRPV4 channel in vivo through the IP3-PKC signalling pathway - Lei Shi; Chenchen Jiang; Hanghang Xu; Jiangping Wu; Jiajun Lu; Yuxiang He; Xiuyun Yin; Zhuo Chen; Di Cao; Xuebin Shen; Xuefeng Hou; Jun Han (Pharmaceutical Biology, 2023)
AbstractContext Hyperoside (Hyp), one of the active flavones from Rhododendron (Ericaceae), has beneficial effects against cerebrovascular disease. However, the effect of Hyp on vasodilatation has not been elucidated.Objective To explore the effect of Hyp on vasodilatation in the cerebral basilar artery (CBA) of Sprague-Dawley (SD) rats suffering with ischaemic–reperfusion (IR) injury.Materials and methods Sprague-Dawley rats were randomly divided into sham, model, Hyp, Hyp + channel blocker and channel blocker groups. Hyp (50 mg/kg, IC50 = 18.3 μg/mL) and channel blocker were administered via tail vein injection 30 min before ischaemic, followed by 20 min of ischaemic and 2 h of reperfusion. The vasodilation, hyperpolarization, ELISA assay, haematoxylin–eosin (HE), Nissl staining and channel-associated proteins and qPCR were analysed. Rat CBA smooth muscle cells were isolated to detect the Ca2+ concentration and endothelial cells were isolated to detect apoptosis rate.Results Hyp treatment significantly ameliorated the brain damage induced by IR and evoked endothelium-dependent vasodilation rate (47.93 ± 3.09% vs. 2.99 ± 1.53%) and hyperpolarization (–8.15 ± 1.87 mV vs. −0.55 ± 0.42 mV) by increasing the expression of IP3R, PKC, transient receptor potential vanilloid channel 4 (TRPV4), IKCa and SKCa in the CBA. Moreover, Hyp administration significantly reduced the concentration of Ca2+ (49.08 ± 7.74% vs. 83.52 ± 6.93%) and apoptosis rate (11.27 ± 1.89% vs. 23.44 ± 2.19%) in CBA. Furthermore, these beneficial effects of Hyp were blocked by channel blocker.Discussion and conclusions Although Hyp showed protective effect in ischaemic stroke, more clinical trial certification is needed due to the difference between animals and humans.